(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The present study deals with the trends in Epilepsy Disease at the world perspective. The aim of this study is to elaborate the scientific production of original and review articles published in the Epilepsy Disease journals for the study period 2012 to 2021, considering qualitative and quantitative measures from all over the countries. All the records were downloaded completely from the Web of Science (WoS) online database during the period of study. The total output was 18092 records from 2418 journals. The results show that the year 2021 was considered the most productive with 2546 (14.07%) publications. Among the authors, Striano P has published the highest number of 315 articles. From the study it can be concluded, this paper may be considered as a baseline study for the scientometric information related to articles on Epilepsy Disease published in the Web of Science. Further research using other databases like PubMed, Scopus, Chemical abstract, BIOSIS and Derwent Biotechnology Abstracts could be attempted.